Legal Protection of Notary/PPAT in Making Deeds Based on Fake Information (Case Study of Decision Number: 73/PDT.G/2012/PN.PL) - Khairunnisa Riani Putri; Mella Ismelina Farma Rahayu (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
A Notary is a public official who is authorized to perform certain legal formalities, especially to draw up or certify contracts, deeds, and other documents for use in other jurisdictions. The Land Deed Making Officer or PPAT is a public official who is authorized to make certain deeds related to land belonging to Flats Units. The Notary/PPAT is responsible for upholding integrity and morals. Legal protection and guarantees for the Notary/PPAT are needed for the implementation of the legal service function. Protection is needed to protect Notaries/PPATs who have carried out deed-making activities carefully and professionally in accordance with legal provisions and statutory regulations. Notaries/PPATs often receive false information or documents from parties, so Notaries/PPATs are suspected of being involved in criminal or civil cases. The purpose of this study is to examine the legal provisions for the protection of the position of Notary/PPAT in making Deeds based on False Statements (Case Study of Decision Number 73/PDT.G/2012/PN.PL). The research method uses a normative legal approach with qualitative descriptive data analysis. The results of the study show that Notaries/PPATs have the right to obtain legal protection in order to create legal certainty as public officials whose function is to provide services to the public. Notary/PPAT is not responsible in terms of fraud and mistakes made by the parties. The Notary/PPAT is only in charge of recording what is conveyed by the parties to be further stated in the deed or party. The legal protection provided by the state with regulations or legal rules is considered optimal in protecting Notaries/PPATs.